Analisis Cluster Untuk Pemetaan Status Gizi Balita Puskesmas Lowokwaru Berdasarkan Antropometri - Viry Puspaning Ramadhan; Devita Maulina Putri; Indra Dwi Laksana; Dian Fitri Islamiah Munisah (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This research examines the mapping of nutritional status in toddlers as an important indicator for assessing child health and development, focusing on the Lowokwaru Health Center in Malang. Data shows that the mapping of nutritional status is still not accurate, prompting this study to identify toddlers at risk of stunting and design appropriate interventions. Quick and accurate mapping of nutritional status is crucial for reducing the risk of stunting and preventing malnutrition in toddlers. The data used comes from anthropometric measurements, including height-for-age (HAZ), weight-for-height (WHZ), and weight-for-age (WAZ). The method applied is K-Means clustering, where, after preprocessing the data, the researchers determine the number of clusters and centroids. Grouping is conducted by calculating Euclidean distance. The results indicate that 75% of toddlers at the Lowokwaru Health Center are experiencing excess nutrition and are at risk of stunting. These findings provide a strong basis for enhancing interventions and preventing stunting in the region.